The Relationship between Statin Intake and Risk of Pancreatic Cancer: A Systematic Review and Meta-analysis - Bagheri, Hesamaldin; Adeli, Omid-Ali; Heidari-Soureshjani, Saeid; Azadegan-Dehkordi, Zahra; Sherwin, Catherine MT (Current Drug Research Reviews, 2025)
BackgroundPancreatic neoplasm is one of the types of cancer with a high incidence and case-fatality rate.ObjectivesThis study was designed to investigate the relationship between statin intake and the risk of pancreatic cancer with a systematic review and meta-analysis approach.MethodsThis study was a systematic review and meta-analysis of studies published before 2023 in Cochrane Library, Web of Science (WOS), PubMed, Google Scholar, ScienceDirect, Scopus, and Embase databases. The statistical analyses were conducted using Stata software, version 15. The significance level for this study was set at 0.05.ResultsThis meta-analysis included 32 studies and a total of 5,849,814 participants. The risk ratio (RR) of pancreatic cancer in comparison to the non-statin receiving group in statin users in total was equal to 0.75 (95% CI: 0.66-0.86, p-value <0.001), in the cohort studies was obtained to be 0.70 (0.53-0.93), in the randomized clinical trials (RCTs) had a ratio of 0.99 (0.53-1.86), while studies conducted in American countries had a ratio of 0.69 (0.51-0.93), studies in Asian countries had a ratio of 0.73 (0.56-0.97), and studies in European countries had a ratio of 0.88 (0.76-1.02). Furthermore, the study did not detect any signs of publication bias.ConclusionThe study findings suggest a potential connection between using statins and a lower risk of pancreatic cancer. However, it is important to note that controlled clinical trials did not find a statistically significant association between taking statins and the development of pancreatic cancer. Therefore, it is advisable to exercise caution when interpreting the results of this study.
Keywords: pancreatic cancer